Beamline B21: high‐throughput small‐angle X‐ray scattering at Diamond Light Source. (18th August 2020) - Cowieson, Nathan P.; Edwards-Gayle, Charlotte J. C.; Inoue, Katsuaki; Khunti, Nikul S.; Doutch, James; Williams, Eugene; Daniels, Steven; Preece, Geoff; Krumpa, Nicholas A.; Sutter, John P.; Tully, Mark D.; Terrill, Nick J.; et al.
Abstract : The B21 beamline at Diamond Light Source is optimized for automated measurement of small‐angle X‐ray scattering from solution samples. Abstract : B21 is a small‐angle X‐ray scattering (SAXS) beamline with a bending magnet source in the 3 GeV storage ring at the Diamond Light Source Ltd synchrotron in the UK. The beamline utilizes a double multi‐layer monochromator and a toroidal focusing optic to deliver 2 × 10 12 photons per second to a 34 × 40 µm (FWHM) focal spot at the in‐vacuum Eiger 4M (Dectris) detector. A high‐performance liquid chromatography system and a liquid‐handling robot make it possible to load solution samples into a temperature‐controlled in‐vacuum sample cell with a high level of automation. Alternatively, a range of viscous or solid materials may be loaded manually using a range of custom sample cells. A default scattering vector range from 0.0026 to 0.34 Å −1 and low instrument background make B21 convenient for measuring a wide range of biological macromolecules. The beamline has run a full user programme since 2013.